Requirement and functional redundancy of two large ribonucleotide reductase subunit genes for cell cycle, chloroplast biogenesis and photosynthesis in tomato. (14th June 2022) - Gu, Mengjun; Lu, Qiao; Liu, Yi; Cui, Man; Si, Yaoqi; Wu, Huilan; Chai, Tuanyao; Ling, Hong-Qing
Abstract: Background and Aims: Ribonucleotide reductase (RNR), functioning in the de novo synthesis of deoxyribonucleoside triphosphates (dNTPs), is crucial for DNA replication and cell cycle progression. In most plants, the large subunits of RNR have more than one homologous gene. However, the different functions of these homologous genes in plant development remain unknown. In this study, we obtained the mutants of two large subunits of RNR in tomato and studied their functions. Methods: The mutant ylc1 was obtained by ethyl methyl sulfonate (EMS) treatment. Through map-based cloning, complementation and knock-out experiments, it was confirmed that YLC1 encodes a large subunit of RNR (SlRNRL1). The expression level of the genes related to cell cycle progression, chloroplast biogenesis and photosynthesis was assessed by RNA-sequencing. In addition, we knocked out SlRNRL2 (a SlRNRL1 homologue) using CRISPR-Cas9 technology in the tomato genome, and we down-regulated SlRNRL2 expression in the genetic background of slrnrl1-1 using a tobacco rattle virus-induced gene silencing (VIGS) system. Key results: The mutant slrnrl1 exhibited dwarf stature, chlorotic young leaves and smaller fruits. Physiological and transcriptomic analyses indicated that SlRNRL1 plays a crucial role in the regulation of cell cycle progression, chloroplast biogenesis and photosynthesis in tomato. The slrnrl2 mutant did not exhibit any visible phenotype. SlRNRL2 has a redundant function with SlRNRL1, and the double mutant slrnrl1slrnrl2 is lethal. Conclusions: SlRNRL1 is essential for cell cycle progression, chloroplast biogenesis and photosynthesis. In addition, SlRNRL1 and SlRNRL2 possess redundant functions and at least one of these RNRLs is required for tomato survival, growth and development.